Immigrants and Mortgage Delinquency in the United States - Zhenguo Lin; Yingchun Liu; Jia Xie (Bank of Canada, 2015)
We investigate the relationship between immigrant status and mortgage delinquency in the United States. We find that after controlling for observables, newly arrived immigrants are likely to have a higher delinquency rate on mortgages than natives, while immigrants who have resided in the United States for more than 20 years are no different than natives in this regard. In addition, there is no evidence that the second generation of immigrants has a higher delinquency rate than the third-or-higher generation. Our results are robust to potential sample selection bias and functional misspecifications.
Keywords: J15; G21; 330; Debt management; Financial stability